Educational Attainment and Ischemic Stroke: A Mendelian Randomization Study - Gao, Luyan; Wang, Kun; Ni, Qing-Bin; Fan, Hongguang; Zhao, Lan; Huang, Lei; Yang, Mingfeng; Li, Huanming (Frontiers in Genetics, 2022)
Observational studies have evaluated the potential association of socioeconomic factors such as higher education with the risk of stroke, however reported controversial findings. The objective of our study was to evaluate the potential causal association between higher education and the risk of stroke. Here, we performed a Mendelian randomization analysis to evaluate the potential the association of educational attainment with ischaemic stroke (IS) using large-scale GWAS datasets from Social Science Genetic Association Consortium (SSGAC, 293,723 individuals), UK Biobank (111,349 individuals) and METASTROKE consortium (74,393 individuals). We selected three Mendelian randomization methods including inverse-variance weighted meta-analysis (IVW), weighted median regression, and MR-Egger regression. IVW showed that each additional 3.6 years increase in years of schooling was significantly associated with a reduced IS risk (OR=0.54, 95% CI: 0.41-0.71, and P=1.16×10−5). Importantly, the estimates from weighted median (OR=0.49, 95% CI: 0.33-0.73, and P=1.00×10−3), and MR-Egger estimate (OR=0.18, 95% CI: 0.06-0.60, and P=5.00×10−3), were consistent with the IVW estimate in terms of direction and magnitude. In summary, we provide genetic evidence that high education could reduce IS risk.